2005
DOI: 10.1111/j.1399-3038.2005.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo‐controlled trial comparing montelukast and cetirizine for treating perennial allergic rhinitis in children aged 2–6 yr

Abstract: Leukotriene receptor antagonists (LTRAs) were recently added to the method of treating allergic rhinitis (AR). However, in children under 6 yr old, there has been no study about its efficacy in treating AR. We aim to compare the clinical efficacy of montelukast, cetirizine and placebo in the treatment of children from 2 to 6 yr old with perennial allergic rhinitis (PAR), to see if there are any significant differences. Sixty children were selected and treated with montelukast, or cetirizine, or placebo once da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 26 publications
0
65
0
Order By: Relevance
“…Symptoms of congestion are only effectively controlled by nasal corticosteroids (120) (B). In children, there are insufficient comparative data to determine whether antihistamines or montelukast is more effective, although some studies indicate that antihistamines are more effective for itching (121,122). Antihistamines and montelukast may provide some additional benefit when used as add-on therapy with nasal corticosteroids (73, 74, 118, 120)(B).…”
Section: Relative Effectiveness Of Different Pharmacological Approachmentioning
confidence: 99%
“…Symptoms of congestion are only effectively controlled by nasal corticosteroids (120) (B). In children, there are insufficient comparative data to determine whether antihistamines or montelukast is more effective, although some studies indicate that antihistamines are more effective for itching (121,122). Antihistamines and montelukast may provide some additional benefit when used as add-on therapy with nasal corticosteroids (73, 74, 118, 120)(B).…”
Section: Relative Effectiveness Of Different Pharmacological Approachmentioning
confidence: 99%
“…42 A randomized placebo-controlled trial has also shown efficacy of montelukast in comparison to placebo in total nasal symptom scores and a quality of life questionnaire in children 2-6 years of age. 43 Studies have also shown the effectiveness of montelukast in comparison to placebo in both seasonal and perennial AR patients in both adults and children as part of trials that evaluated montelukast in combination with other medications. 44,45 This improvement included the control of daily symptoms of nasal congestion, itching, sneezing and rhinorhea as well as other endpoints such as eye symptoms, global evaluations, nighttime symptom scores and quality of life surveys.…”
Section: Clinical Trials Comparing Montelukast To Placebomentioning
confidence: 99%
“…56 In children 2-6 years old, montelukast was equivalent to cetirizine in the management of nasal symptoms of perennial AR except for nasal itching which was better controlled with cetirizine. 43 Montelukast in combination with cetirizine showed better control of the clinical nasal symptoms and reduced eosinophil counts better than either montelukast or cetirizine alone in seasonal AR patients. 57 When given 6 weeks before the start of the pollen season this combination delayed the onset of allergic seasonal symptoms in comparison to monotherapy.…”
Section: Combination Therapymentioning
confidence: 99%
“…[24][25][26] Clinical allergic symptoms as well as eosinophil count, serum IgE, and IL-4 levels have been shown to drop significantly after LTRA treatment in children with allergic rhinitis and Kimura's disease. [27][28][29] The effectiveness of LTRAs was also reported in allergic eosinophilic esophagitis, a rarely diagnosed condition involving eosinophil infiltration of the esophageal mucosa among infants. [30] Serum IgE levels were significantly increased in the control group as a natural course of illness despite dietary treatment, but were significantly decreased in the LTRA group.…”
Section: Il-4 and Il-5)mentioning
confidence: 99%